Linguistic Variation Issues: Case and Agreement in Northern Russian Participial Constructions - Civardi, Antonio (Biblioteca di Studi di Filologia Moderna, 2016)
This study offers a novel approach to a longstanding problem in Slavic Linguistics, the formal representation of the Northern Russian participial constructions in -n(o)/-t(o). Unlike previous works, the methodological stance adopted by the author focuses on singling out all the relevant patterns of variation and on pursuing a unified explanation for them. The key to the solution of the puzzle is the idea that the participial affix -n-/-t- and the agreement inflections are not just pieces of morphology inserted post-syntactically, but true heads that enter the computation and are able to manipulate the argumental roles of the verb and to check the EPP. The author's proposal is properly framed in the context of current debate on interlanguage variation.